Pembelajaran berbasis karakter untuk meningkatkan daya saing dalam era global bagi siswa di daerah terdepan, terluar, dan tertinggal (studi kasus di Kalimantan Utara, Sulawesi Utara, NTT, dan Papua) - Asis Wahyudi; Mohammad Haris Muzakki; Juliyansyah Juliyansyah (Jurnal Teori dan Praksis Pembelajaran IPS, 2016)
Indonesia consists of various regions separated by the Strait and the sea, both the outer islands and the outlying and less developed regions (3T). This contributed to difficulties in the distribution of development efforts, due to the distance that must be taken to reach the center of government. These conditions cause uneven quality of education. Thus, it is necessary to enhance the quality of education in the outer islands and the outermost regions lagging through character education for students. However, the reality is not in accordance with the appropriate conditions. This paper aims to identify the conditions of the students in the outermost, and lags well as analyzing the corresponding character based learning applied to students in order to increase competitiveness in the global era in the outermost regions leading and lagging. Data obtained through observation, interviews, and documentation and analyzed descriptively. The results showed that the character of the students in the outermost, and behind is a lack of patriotism, hard work, creativity, responsibility, discipline, and love to read. Character-based learning are applied to students in the area 3T is the integration of character education in schools and subject culture, such as an increased sense of patriotism through the use of Indonesian was good and true in every learning and always start with singing the national anthem. As for the low character of hard work can be enhanced through the provision of motivation on the importance of learning and schools for future students.Keywords: Character Education; Students; Regions Frontier, Outermost, and Disadvantaged http://dx.doi.org/10.17977/um022v1i12016p001